Incidence and seasonality of respiratory viruses among medically attended children with acute respiratory infections in an Ecuador birth cohort, 2011–2014. Issue 1 (25th August 2021) - Azziz‐Baumgartner, Eduardo; Bruno, Alfredo; Daugherty, Michael; Chico, Martha E.; Lopez, Andrea; Arriola, Carmen Sofia; de Mora, Domenica; Ropero, Alba María; Davis, William W.; McMorrow, Meredith; Cooper, Philip J.
Abstract: Background: Ecuador annually has handwashing and respiratory hygiene campaigns and seasonal influenza vaccination to prevent respiratory virus illnesses but has yet to quantify disease burden and determine epidemic timing. Methods: To identify respiratory virus burden and assess months with epidemic activity, we followed a birth cohort in northwest Ecuador during 2011–2014. Mothers brought children to the study clinic for routine checkups at ages 1, 2, 3, 5, and 8 years or if children experienced any acute respiratory illness symptoms (e.g., cough, fever, or difficulty breathing); clinical care was provided free of charge. Those with medically attended acute respiratory infections (MAARIs) were tested for common respiratory viruses via real‐time reverse‐transcription polymerase chain reaction (rRT‐PCR). Results: In 2011, 2376 children aged 1–4 years (median 35 months) were enrolled in the respiratory cohort and monitored for 7017.5 child‐years (cy). The incidence of respiratory syncytial virus (RSV) was 23.9 (95% CI 17.3–30.5), influenza 10.6 (2.4–18.8), adenoviruses 6.7 (4.6–28.0), parainfluenzas 5.0 (2.3–10.5), and rhinoviruses, bocaviruses, human metapneumoviruses, seasonal coronaviruses, and enteroviruses <3/100 cy among children aged 12–23 months and declined with age. Most (75%) influenza detections occurred April–September. Conclusion: Cohort children frequently had MAARIs, and while the incidence decreased rapidly among older children, more than one in five children aged 12–23 months tested positive for RSV, and one in 10 tested positive for influenza. Our findings suggest this substantial burden of influenza occurred more commonly during the winter Southern Hemisphere influenza season.